Relationship between Pay Level, Pay Structure and Job Commitment in Malaysian Public Community College: The Mediation Role of Distributive Justice - Ismail, Azman; Ismail, Yusof; Ibrahim, Zalina; Leng, Clara Ong Guat; Kiong, Perry Tan Chee (The South East Asian Journal of Management, 2009)
This study was conducted to measure the mediating effect of distributive justice on the relationship between pay level, pay structure, and job commitment. A survey research method was used to gather 194 usable questionnaires from academic staff of 15 Malaysian public community colleges (MPCC). Outcomes of testing mediating model using a stepwise regression analysis showed that distributive justice has increased the effect of pay design features (i.e., pay level and pay structure) on job commitment. This result confirms that distributive justice does act as a full mediating variable in the pay design models of the organizational sector sample. In addition, implications of this study to compensation theory and practice, methodological and conceptual limitations, as well as directions for future research are discussed.